EXPERIMENTAL STUDY OF THE ELASTIC PROPERTIES OF HVS PAPER AT VARIOUS PULLING SPEEDS - Fransiska Njo, Angeli
Tensile testing is a commonly used material testing method to determine the mechanical properties of materials such as tensile strength, modulus of elasticity, and ductility. Tensile test results are essential for structural design and analysis. Tensile testing is also often utilized in education as a practical learning module to understand the relationship between force, strain, and stress directly. This study aims to examine the effect of tensile speed variation on the elasticity properties of HVS paper, with a focus on tensile strength, modulus of elasticity, and ductility. Based on observations of the tensile test experimental module at the Physics Study Program of the Bandung Institute of Technology, and referring to previous studies showing that the stress-strain curve is sensitive to the strain rate, this study used HVS paper for efficiency and ease of the testing process. In this experiment, tensile tests were conducted with a pulling speed between 10 mm/min to 80 mm/min. The experiment was conducted in 10 repetitions and the results showed a variation in the measurement data for each different tensile speed variation. The results show that the tensile strength increases with the pulling speed. The maximum strain also increased but not significantly. The elastic modulus did not show a consistent increase with higher pulling speed.